2020
DOI: 10.22436/jmcs.023.01.03
|View full text |Cite
|
Sign up to set email alerts
|

Some new results for Horn's hypergeometric functions Γ 1 and Γ 2

Abstract: The object of the present work is to deduce several important developments in various recursion relations, relevant differential recursion formulas, infinite summation formulas, integral representations, and integral operators for Horn's hypergeometric functions Γ 1 and Γ 2 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…Our paper is generally based on the extension of Horn's hypergeometric functions of two variables. A few specializations relevant to the present discussion have also been derived from results of papers [33][34][35]38]. We focused on the generalization of the Horn's function G B of three variables and presented some partial differential equations, differential recursion formulas, series representations, integral representations and infinite summations.…”
Section: Infinite Summations For G Bmentioning
confidence: 99%
See 1 more Smart Citation
“…Our paper is generally based on the extension of Horn's hypergeometric functions of two variables. A few specializations relevant to the present discussion have also been derived from results of papers [33][34][35]38]. We focused on the generalization of the Horn's function G B of three variables and presented some partial differential equations, differential recursion formulas, series representations, integral representations and infinite summations.…”
Section: Infinite Summations For G Bmentioning
confidence: 99%
“…In our present work, we establish some new differentiation formulas, differential equations, recursion relations, differential recursion relations, confluence formulas, series representations, integration formulas, and infinite summations for the Horn hypergeometric function G B of three variables by using the technique of Ibrahim [25], Ibrahim and Rakha [26], Rakha and Ibrahim [27], Rakha et al [28], Kim et al [29] and Brychkov and Savischenko [30][31][32]. Pathan et al [33], and Shehata and Shimaa [34,35] found 7 and 11 hypergeometric series in two variables of order two. We shall derive these G B series from our viewpoint.…”
Section: Introduction and Notationsmentioning
confidence: 99%